2015
DOI: 10.1186/s13012-015-0214-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of evidence and context for implementing a multimodal intervention to increase HIV testing

Abstract: BackgroundIncreasing the use of routine preventive care such as HIV testing is important, yet implementation of such evidence-based clinical care is complex. The Promoting Action on Research Implementation in Health Services (PARiHS) model for implementation posits that implementation will be most successful when the evidence, context, and facilitation strategies are strong for the clinical practice. We evaluated the relative importance of perceived evidence, context, and facilitation of HIV testing during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 22 publications
1
30
0
1
Order By: Relevance
“…For instance, promising educational models such as group education programs delivered by allied health professionals, peer education models, and directly delivered early intervention models (e.g., Senior HIV Intervention Project) could be culturally tailored for older African American PLWH to increase their testing rates and HIV risk awareness [55]. Provider-based interventions also have the potential to increase testing among older African Americans including those that educate providers about up-to-date clinical recommendations for HIV screening and testing, and promote sexual risk assessments, risk-reduction counseling, and HIV testing [56].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, promising educational models such as group education programs delivered by allied health professionals, peer education models, and directly delivered early intervention models (e.g., Senior HIV Intervention Project) could be culturally tailored for older African American PLWH to increase their testing rates and HIV risk awareness [55]. Provider-based interventions also have the potential to increase testing among older African Americans including those that educate providers about up-to-date clinical recommendations for HIV screening and testing, and promote sexual risk assessments, risk-reduction counseling, and HIV testing [56].…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 , 12 ] Although many older adults opt out of HIV testing, [ 4 , 13 ] providers often do not offer HIV tests to older adults [ 14 , 15 ] due to ageist assumptions about older adults’ sexual or drug use behaviors. [ 14 , 16 ] As a result, older adults infected with HIV are more likely than younger people to go undiagnosed or be diagnosed later in the disease course. [ 13 , 17 , 18 ]…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the UK, a meta‐analysis published in 2014 found that the pooled estimate of eligible people offered an HIV test was 9.3% (95%CI 1.2% to 17.3%) in patients diagnosed with an indicator disease, and in people attending screening settings was 29.5% (95%CI 23.6% to 35.4%); in the US in areas of ≥0.1% prevalence, only 25 health care settings (6.6%) reported screening all patients for HIV, whereas 131 (34.8%) reported screening only some patients . To assess barriers and facilitators is useful for understanding how different facilitation strategies may be effective in implementing disease screening and testing in primary care, and there are experiences that demonstrate that interventions to increase HIV testing can be successful when utilizing proven quality improvement techniques …”
Section: Introductionmentioning
confidence: 99%